Effect of ashing method on some micronutrients in black sesame seeds (Sesamum indicum). Issue 2 (4th March 2014) - Qadeer, Aneela; Anwer, Humera; Mahmood, Talat; Abbas Bhutto, Muhammad
Abstract : Purpose: – Nutritional and medicinal properties of black sesame seeds ( Sesamum indicum ) make it very valuable in traditional system of food. Minerals in Sesamum indicum play an important role to enhance its nutritional value. The present research comprises on proximate and chemical analysis of Sesamum indicum . This study is also based on the development of ashing methods for extraction of metals in black sesame seeds. The paper aims to discuss these issues. Design/methodology/approach: – Black sesame seeds were taken from local market at Karachi-Pakistan. Proximate analysis of seeds comprises of moisture content, ash content and total metal content by EDTA titration. Digestion of this herb was done in different medium, i.e. HNO3, HCl, H2 SO4 and simple ash (ash was prepared without using any acid). Atomic absorption spectroscopy was used for the analysis of metals, i.e. Fe, Zn, Cu and Mg in all these ashes. Findings: – From the results it is concluded that best medium for ashing is H2 SO4, by which maximum ash (5.39±0.0021 per cent) produced. Qualitative analysis (based on Ksp values) also confirmed the presence of maximum number of metals in H2 SO4 medium. Complexometric titration also revealed that maximum metal content was found to be in HCl and H2 SO4 ash. Results from atomic absorption spectroscopy revealed that H2 SO4 is the best method for copper (0.399±0.0001 mg/g) and iron (0.3993±0.0015 mg/g), while simple ash can extract zinc and magnesium at their maximum level. Originality/value: – This research demonstrates the best ashing method for the extraction of micronutrients, present in Sesamum indicum . These micronutrients are very beneficial for human health.